In Silico Study and Pharmacokinetics Prediction of ɛ-Viniferin Compound as Anticancer Drug Candidate - Dewi, I Gusti Ayu Intan Puspita; Yuda, Putu Era Sandhi Kusuma; Rahadi, I Wayan Surya (Jurnal Kefarmasian Indonesia, 2023)
The ɛ-Viniferin (ɛ-VNF) is a resveratrol dimer found in grapes (Vitis vinifera) which is thought to have anticarcinogenic activity. Breast cancer is one of the biggest causes of mortality in women. Current conventional chemotherapy can give negative side effects for cancer patients. Therefore, exploration to find an alternative modality is required. HER2 (Human Epidermal Growth Factor Receptor 2) and CDK6 (Cyclin Dependent Kinase 6) are two proteins that play an important role in breast cancer cell proliferation and differentiation. This study aimed to determine the potential of ɛ-VNF in inhibiting HER2 and CDK6 by molecular docking study. This research was conducted in silico using AutoDockTools v1.5.7 software. The results were validated with PyMOL and visualized in Discovery Studio Visualizer software to see the amino acid residues generated. Prediction of pharmacokinetics and toxicity profiles of the compound were performed with SwissADME and ADMETLab web tools. The results showed that ɛ-VNF was able to bind to HER2 and CDK6 receptors with binding energies of -10,45 kcal/mol and -7,56 kcal/mol, respectively. In silico pharmacokinetics and toxicity studies showed that ɛ-VNF fulfills Lipinski’s Rule of Five and has the potential to be used as a drug candidate. Overall, the results of this study indicate that ɛ-VNF has the potential to be further investigated and developed as an anticancer drug candidate through inhibition of HER2 and CDK6 receptors.